Keterampilan Berbahasa “Membaca Intensif” Siswa Kelas X SMA Negeri 1 Teluk Meranti - Alda Alawiyah; Nazirun Nazirun (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The problem discussed in this study is How to Find Reading Information for Class X Students of SMA Negeri 1 Teluk Meranti, Teluk Meranti District, Pelalawan Regency for the 2020/2021 Academic Year. This study aims to describe, analyze, interpret, and conclude information and data about intensive reading skills in determining main ideas, explanatory ideas, and reading conclusions for class X students of SMA Negeri 1 Teluk Meranti, Teluk Meranti District, Pelalawan Regency for the Academic Year 2020/2021, the population in This research is all X IPA totaling 22 people. The sample used is a full/saturated sample. The theory used is Henry Thunder Tarigan (2008). Abdul Razak (2005), Dp. Tampubolon (2015). The results of the intensive reading ability research in finding reading information for class X students of SMA Negeri 1 Teluk Meranti, Teluk Meranti District, Pelalawan Regency in determining main ideas, explanatory ideas, and reading conclusions. The method used in this research is secondary and quantitative research approach. Determining the main ideas in the reading text in the sufficient category (75.15%), determining the explanatory ideas in the reading text in the sufficient category (67.50%), determining the conclusions in the reading text in the medium category (62.12%). It can be concluded that the average intensive reading ability to find information in the readings of class X students is an average of 68.26% which is categorized as sufficient and the hypothesis is rejected.